Peran Guru PAI dalam Pembentukan Karakter Kemandirian Anak Berkebutuhan Khusus di SLB Darul Ulum Jogoroto Jombang - Rohmatul Ummah; Iva Inayatul Ilahiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Those who guide others toward a better life in order to elevate their humanity to a higher plane are know as educators. The phrase “character education” is becoming more and more well-know in indonesian society. Event though childern with various problems are gifts from god, children with special needs (ABK) are sometimes viewed as different persons due of their deficiencies, despite the fact that beneath their limits they have many amazing blessings.This study intend to explain how islamic religious education teachers at SLB contribute to the development of the independent character of children with special needs, as well the obstacles and enablers that these teachers encounter along the way Darul Ulum Jogoroto Jombang.A qualitative research approach is the kind of research that is being used. Three metods were employed to acquire the data : documentation, interviews, and observation. Three steps comprised the data analysis process : data reduction, data display, and conclusion drawing. Extended observation methods, increased persistence, data triangulation, and the use of reference matrials are all used to verify the authenticity of the data.The results of the research show that: 1) the role of PAI teachers at SLB Darul Ulum Jogoroto Jombang, namely: educator, teacher, guide, 2) Meanwhile, the role of PAI teachers in forming independence is: Educating, teaching, guiding, model and role model, and evaluator. 2) The factors in forming the independent character of children with special needs at SLB Darul Ulum Jogoroto Jombang, include: a. Supporting factors: Family factors, School environmental factors, The teacher's approach to children with special needs is by using several methods in independent character education, including lecture methods, habituation methods and methods.